Correlation of Fiqih with Sharia Economic Law in Indonesia - Ghiffary Aulia Rahman; Muthoifin (al-Afkar, Journal For Islamic Studies, 2024)
The correlation between Fiqh (the science of Islamic law) and the sharia economic law in Indonesia is the relationship or link between the two fields in the context of religious regulations and practices as well as the rules of law that apply in the sharia economic system.Fiqh is a science that studies the rules of the Islamic religion, including in the economic field. Fiqh provides guidelines on how a Muslim should carry out his economic activities by religious teachings. For example, fiqh regulates halal and haram in business, usury transactions, the distribution of zakat, waqf, and so on.Meanwhile, the sharia economic law in Indonesia was made to regulate financial practices by sharia principles. This law covers various aspects such as sharia banking, insurance, capital market, and investment, and other financial products based on Islamic principles.So it can be said that there is a correlation between Fiqh as a theological and moral foundation for Muslim religious practices and the Sharia Economic Law law as a formal legal instrument to apply fiqh concepts in the world of business and finance.